Efficiency Investigation of A Protection and Correction Solid State Device for Low-Voltage Distribution Networks - Ioannou, Stelios; Marouchos, Christos; Darwish, Mohammed K.; Putrus, Ghanim A. (My University, 2019)
A Solid State device which can limit and interrupt a fault, apply power factor correction and voltage regulation under normal conditions is presented with an investigation of its efficiency. The losses of the switching semiconductors are investigated by employing the PSIM Thermal Module. This work closely investigates the phase shift between the current and voltage waveforms for a 50Hz system and switching frequency of 5kHz before modelling and calculating the IGBT losses. For DC/DC converters the associated currents and voltages are in phase. However, as this work shows for switched capacitor circuits there is a 90° phase shift between current and voltage. Finally, calculated losses are compared to simulated losses as well as to other methodologies suggested in literature.
Keywords: Efficiency; Fault limiting; Losses; Power factor; Switched capacitor; Thermal module